The Role of Progressive Muscle Relaxation Therapy in Mitigating Diabetes Distress and Anxiety in People with Type 2 Diabetes, A Randomized Controlled Study at Independent University Hospital (IUH), Faisalabad, Pakistan - Lubna Sarfraz, Sidra Anwar, Mohsina Hamid, Muhammad Khan Malik, Aliya Waseem, Saba Abrar, Muhammad Jamal (Pakistan Journal of Medical & Health Sciences, 2023)
Background & Objectives: Depression and anxiety are common in type 2 diabetics. Diabetes distress (DD) and anxiety are symptoms. These problems greatly affect their blood glucose control and quality of life. Jacobson’s Progressive Muscle Relaxation (PMR) therapy was tested for its efficacy in treating diabetic dyslipidaemia (T2DM), anxiety, glycaemic control, haemodynamic parameters, and lipid profiles in people with both types of diabetes. Methods: A prospective randomised controlled experiment was undertaken at the Independent University Hospital (IUH) in Faisalabad, Pakistan. After recruiting 80 type 2 diabetics, they were randomly assigned to two groups: the control group (n=40) received general stress counselling, while the intervention group (n=40) received PMR treatment and general counselling. Both groups received equal counselling. The Diabetes Distress Scale (DDS) and Generalised Anxiety Disorder (GAD-7) scores were assessed at the start and three months of the trial. Anthropometry, haemodynamics, and biochemistry were also assessed. Results: A substantial decrease in DDS (4.1 vs. 1.6, p<0.0001) and GAD-7 (18.1 vs. 7.1, p<0.0001) was observed in the intervention group. The control of glycaemic levels improved significantly, with HbA1c (9.2% vs. 7.6%), fasting glucose (195.5 mg/dL vs. 143.3 mg/dL), and postprandial glucose (267.2vs. 174.5 mg/dL) reduced (p = 0.001). Both intervention and control groups showed lipid profile improvements. However, the control group showed no improvement and significantly worsened blood sugar management. Conclusion: PMR therapy improved blood glucose and cholesterol management in type 2 diabetic patients and reduced pain and anxiety. Based on these findings, PMR therapy may be an effective type 2 diabetes treatment. Keywords: Progressive Muscle Relaxation (PMR),Type 2 Diabetes Mellitus (T2DM),Diabetes Distress, Anxiety, Glycemic Control.